2019
DOI: 10.1002/nau.23935
|View full text |Cite
|
Sign up to set email alerts
|

Comparison in the efficacy of fesoterodine or mirabegron add‐on therapy to silodosin for patients with benign prostatic hyperplasia complicated by overactive bladder: A randomized, prospective trial using urodynamic studies

Abstract: Aims To compare the efficacy of fesoterodine or mirabegron add‐on therapy for persistent overactive bladder (OAB) symptoms despite silodosin monotherapy in men with lower urinary tract symptoms suggestive of benign prostatic hyperplasia, in both subjective and objective aspects. Methods A total of 120 patients with persistent OAB symptoms despite silodosin monotherapy were randomized to receive add‐on therapy with fesoterodine (4 mg/day) or mirabegron (50 mg/day) for 12 weeks. At week 12, changes from baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Prior studies have observed a lack of significant association between the presence of DO and the physical symptoms experienced by patients 13 with conventional urodynamic testing detecting DO in only 62% of women complaining of urgency and urge incontinence, 34 questioning the clinical relevance of the presence of DO on UDS testing in the diagnosis and management of OAB. However, there is also ample evidence in the literature to suggest a potentially significant association between DO and OAB, with recent studies finding that bothersome OAB symptoms of urinary frequency and urgency, as scored by clinical questionnaires, were significantly associated with the presence of urodynamic DO 6,7,9,10 . More studies are needed to fully elucidate the etiology of DO and its pathophysiology, as well as its clinical relevance to the presentation of OAB as a whole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have observed a lack of significant association between the presence of DO and the physical symptoms experienced by patients 13 with conventional urodynamic testing detecting DO in only 62% of women complaining of urgency and urge incontinence, 34 questioning the clinical relevance of the presence of DO on UDS testing in the diagnosis and management of OAB. However, there is also ample evidence in the literature to suggest a potentially significant association between DO and OAB, with recent studies finding that bothersome OAB symptoms of urinary frequency and urgency, as scored by clinical questionnaires, were significantly associated with the presence of urodynamic DO 6,7,9,10 . More studies are needed to fully elucidate the etiology of DO and its pathophysiology, as well as its clinical relevance to the presentation of OAB as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…OAB is associated with increased morbidity, mortality, 2 and negative psychological well‐being, 3 with a projected annual healthcare burden of $82.6 billion 4 . Although the etiology of OAB is not well understood, several previous studies have suggested that bothersome OAB symptoms may be associated with the urodynamic finding of detrusor overactivity (DO), 5‐8 characterized as involuntary detrusor contractions during the filling phase of cystometry 8 . While the diagnosis of OAB does not require the presence of DO, OAB symptoms, such as urinary frequency and urgency have been found to be significantly associated with the presence of DO on urodynamics 6,9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…We screened 10 full-text articles and excluded 6 articles that did not meet the inclusion criteria or were not relevant to the question being investigated [12,[19][20][21][22][23] (see Supplementary Material 2). Four studies ultimately met the inclusion criteria were included in the qualitative synthesis of this review [24][25][26][27]. The flow of literature through this assessment process is shown in the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) flowchart (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we found easily obtainable parameters in clinical practice that can predict the presence of DO in male patients with LUTS. It was previously reported that improvement of DO was the most significant factor contributing to subjective symptom improvement for those patients with persistent OAB symptoms who received add‐on therapy with fesoterodine or mirabegron, despite silodosin monotherapy 20 . In addition, Seki et al reported that the presence or absence of DO before TURP influenced the postoperative treatment effects 8 .…”
Section: Discussionmentioning
confidence: 98%
“…It was previously reported that improvement of DO was the most significant factor contributing to subjective symptom improvement for those patients with persistent OAB symptoms who received add-on therapy with fesoterodine or mirabegron, despite silodosin monotherapy. 20 In addition, Seki et al reported that the presence or absence of DO before TURP influenced the postoperative treatment effects. 8 If we can discriminate the presence or absence of DO before treatment, we can select an appropriate treatment option for patients with LUTS/BPE in a timely fashion.…”
Section: Discussionmentioning
confidence: 99%